Successful organizational learning in the management of agricultural research and innovation: The Mexican produce foundations - Ekboir, Javier; Dutrénit, Gabriela; Martínez V., Griselda; Vargas, Arturo Torres; Vera-Cruz, Alexandre O. (International Food Policy Research Institute, 2009)
To be an effective poverty alleviation instrument, agricultural policies (including research, extension, and innovation) must be based on an evolutionary approach that emphasizes experimentation, learning, and active interactions among diverse partners However, most agricultural research and extension policies and institutions in developing countries lack the necessary flexibility to implement such an approach. Instead, they apply uniform recipes and struggle with organizational rigidities and other problems. Notable exceptions to this trend have been the Mexican Produce Foundations (PFs). While most organizations eventually lose their creativity and seldom regain it, the PFs have learned, adapted, and contributed to major and diverse impacts on the Mexican agricultural innovation and research systems. Such impacts came from activities that were peripheral to the PFs’ original purpose of managing funds for a national institute devoted to agricultural research. This research report investigates the success of the PFs, exploring how they have sustained organizational innovation over extended periods and adapted to maximize their impact on the agricultural innovation system. Using a theoretical framework that draws on the literature on innovation systems, complexity theories, and organizational cultures and governance, this study analyzes the factors that allowed the PFs to develop strong innovative capabilities and how these capabilities were affected by changes in the interactions among regulatory frameworks, the federal and state governments and organizational structures, creative individuals, and the history of the processes. Understanding the factors that enabled such unusual behavior will help to improve the design and implementation of innovation and research programs in developing countries. Studying the PFs also offers new insights into the dynamics of innovative organizations and how they relate to innovative capabilities.